The effects of akute antioxidant supplementation on aerobic capacity and high intensity training - Collins, M. G. (Medicine & Science in Sports & Exercise, 1998)
Zielstellung: Untersuchung de Einflusses akuter Antioxidanzsupplementierung auf die maximale aeobe Leistung nach 3 aufeinanderfolgenden Tagen mit intensivem Intervalltraining.